Exploring Influences of Policy Collisions on Transfer Student Access: Perspectives From Street-Level Bureaucrats. (December 2020) - Grote, Dustin M.; Knight, David B.; Lee, Walter C.; Watford, Bevlee A.
States and institutions increasingly rely on articulation agreements to streamline vertical transfer, although the effectiveness of those policies on transfer student outcomes remains unclear. To better understand this effectiveness, we explored a partnership between the College of Engineering at a mid-Atlantic research university and two community colleges located within the same state. We interviewed engineering faculty and academic advisors (i.e., the street-level bureaucrats who implement policy) to explore how an articulation agreement influences processes and policies related to coursework transfer. Our results revealed complexities in the implementation of the articulation policy as it collides with an enrollment management university policy that differs in purpose. Their collision has challenging implications for transfer students and for the faculty and advisors responsible for interfacing with those students.